KERJA SAMA TRILATERAL PENGAMANAN MARITIM FILIPINA MALAYSIA INDONESIA DI LAUT SULU TAHUN 2014-2016 - Rahmadhani, Lidiana Febie; Fasisaka, Idin; Widya Nugraha, A. A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This research aims to analyze the Philippine decision to cooperate with Indonesia and Malaysia in overcoming the Abu Sayyaf separatist group. The increasing intensity of the kidnapping by separatist group does not only threaten the security of Philippine citizens but also foreign nationals. This research used qualitative descriptive methods to analyze the issues. This research addresses the problem that answers the question of what are the driving factors of the Philippines in accepting the initiative of cooperation in maritime security in the Sulu Sea with Indonesia and Malaysia. This research used collected data from various sources including, literary sources, news and reports. Data were analyzed with cooperative security and separatism concept in international relations. This research see that the Philippine decision to accept the initiative to cooperate in maritime security by Indonesia as a form of resolving a problem that requires a joint commitment to safeguard their national security. Keywords: Sulu Sea, Cooperative Security, Separatism